SEISMIC ANISOTROPY BENEATH THE CONTINENTS: PROBING THE DEPTHS OF GEOLOGY - Silver P.G. (My University, 1996)
Seismic anisotropy beneath continents is analyzed from shear-wave splitting recorded at more than 300 continental seismic stations. Anisotropy is found to be a ubiquitous property that is due to mantle deformation from past and present orogenic activity. The observed coherence with crustal deformation implies that the mantle plays a major, if not dominant, role in orogenies. No evidence is found for a continental asthenospheric decoupling zone, suggesting that continents are coupled to general mantle circulation.